(3GdaUhd GdegeI aj eYQaI GdGKfG YTQ GdCFeIs - (3fhQ GdOjf Ydj Hf eMeO Hf CMeO Hf GdUHGZ GdeZQHj Gdecj GdeGdcj,J (B855 (3g` s ((3GdRjf Hf eMeO Hf GdhLjg Hf GdRjf GdTGaYi GdeNGFi GdeZQHi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd ef UdGM gPg GdCTeI fUH GdEeGe GdYGOd (B,(3HYO aYf di Cf CPcQ ai cJGHi gPG aUhdkG egeI , ai eYQaI GdCFeI , CYjfi GdCKfG YTQ s
(3BNQgG (B:s
(3bGd HYV Cgd GdCKQ (B: (3GdegOi gh GdbGFe GdefJXQ jSQ YO dg ai GdBCaGb ajchf CVhGA ef GdHOQ GdefjQ ai eSjQg GfJgi Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B111s
(3HChdgG JedjcGJ ZjQ eDQNIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJGQjNs